Knowledge, attitudes, and barriers of a cohort of Iraqi dental practitioners towards the use of silver diamine fluoride in children - Aseel HMJ Al Haidar; Omar A Bawazir (Journal of Baghdad College of Dentistry, 2025)
Background: Silver diamine fluoride (SDF) has attracted increasing attention.